THE EFFECT OF EDUCATION ON THE APPLICATION OF PPE FOR HIV POLY AND TB POLI OFFICERS ON THE RISK OF HEALTH INFECTIONS AT THE KLARI COMMUNITY HEALTH CENTER, KARAWANG REGENCY - Wieke Widhiantika; Jumaedi, Jumaedi; Chaerani Tri Yuliana; Muhidin, Muhidin; Wendi Darmawan (Bajang Institute, 2023)
The correct use of Personal Protective Equipment (PPE) is an essential measure in preventing nosocomial infections within healthcare facilities. This study aims to evaluate the effectiveness of educational interventions on the proper application of PPE in improving compliance among healthcare workers in the HIV and TB clinics at the Klari Subdistrict Health Center, Karawang Regency. A quasi-experimental method was employed, utilizing a pretest-posttest design with a control group. A total of 30 healthcare workers were included as the study sample, divided into experimental and control groups. The educational intervention was conducted over two days, involving intensive training, simulations, and discussion sessions. The study results showed a significant increase in PPE compliance in the group that received the educational intervention, from 40% before the intervention to 60% afterward. Additionally, the proportion of healthcare workers with partial non-compliance decreased from 35% to 25%, while those who did not use PPE at all decreased from 25% to 15%. These findings highlight the importance of structured and continuous education in raising awareness and compliance among healthcare workers regarding PPE use, as well as the role of supervision and adequate PPE availability in maintaining consistent adherence to safety protocols. This study is expected to serve as a reference for the Health Office and other healthcare institutions in developing policies to improve occupational safety for healthcare workers